Comparison of Cervical Cancer Radiation in Bladder Organs with 10 MV LINAC Energy Radiotherapy Using 3DCRT and IMRT Techniques at Sanglah Hospital Denpasar - Asri, Yuli; Sutapa, Gusti Ngurah; Sudarsana, I Wayan Balik; Irhas, Rozi (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2022)
A study has been conducted on comparative analysis of cervical cancer radiation to the bladder organ with 10 MV energy LINAC (Linear Accelerator) radiotherapy using the 3DCRT (Three Dimension Conformal Radiotherapy) technique and the IMRT (Intensity Modulated Radiation Therapy) technique at Sanglah Hospital, Denpasar. The 3DCRT and IMRT techniques were compared by analyzing the values ??of the HI (Homogeneity Index), CI (Conformity Index) and radiation dose distribution in the OAR (Organ At Risk), namely the bladder. The data used are 30 cervical cancer patient data with 10 MV photon beam radiotherapy planning and a total radiation dose of 5000 cGy. In calculating the HI and CI values, the data used were radiation dose of 98%, 50%, 2% of target volume and 95% volume on PTV and the average dose on Bladder organs. The data was obtained from the DVH (Dose Volume Histogram) statistics contained in the TPS (Treatment Planning System). The results of the HI value of 0.0818 for the 3DCRT technique and 0.0899 for the IMRT technique with statistical test results obtained the Asimp.Sig (2-tailed) value of 0.056> 0.05 which means it is not significant, while for the results of the CI value of 0.9500 for the 3DCRT technique and 0.9499 for the IMRT technique with statistical test results obtained the Asimp.Sig (2-tailed) value of 0.970> 0.05 which means it is not significant, meanwhile the percentage of the average dose in the bladder organ obtained an average result from the 3DCRT and IMRT irradiation techniques, 96% and 88%, respectively, with statistical test results, the Asimp.Sig (2-tailed) value was 0.000 <0.05, which was significant. Cervical cancer radiation using the IMRT technique is better than the 3DCRT technique because the IMRT technique minimizes the absorbed dose in OAR, it can be seen from the percentage of the average dose in the bladder organ with the IMRT technique getting a smaller dose percentage.